2(x-4)=3(5-2x)+1

Simple and best practice solution for 2(x-4)=3(5-2x)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-4)=3(5-2x)+1 equation:


2(x-4)=3(5-2x)+1

We simplify the equation to the form, which is simple to understand
2(x-4)=3(5-2x)+1

Reorder the terms in parentheses
+(+2x-8)=3*(5-2x)+1

Remove unnecessary parentheses
+2x-8=+3+*(+5-2x+)+1

Reorder the terms in parentheses
+2x-8=+(+15-6x)+1

Remove unnecessary parentheses
+2x-8=+15-6x+1

We move all terms containing x to the left and all other terms to the right.
+2x+6x=+15+1+8

We simplify left and right side of the equation.
+8x=+24

We divide both sides of the equation by 8 to get x.
x=3

See similar equations:

| -9x^2+36x+13=0 | | 2x+18=11x-54 | | 3X^2-30X+12=0 | | 254-5x=40x+24 | | 118-6x=2x+14 | | 2x^2-55x+15=122 | | -5t-7t=144 | | 49y^2-4=0 | | 49y^2-4= | | 7y+18y= | | 6r-5=7-2r | | 7y+8y= | | 10u^5x^8y+25xy^4=0 | | 64a^2b^3+27a^5=0 | | m=4h+1 | | 5x^2-3=6x | | 74=-p | | -152-10x=7x+16 | | y+3x=6 | | 9c=-63 | | 109-4x=4x+21 | | -24+8= | | 3a+4b-2a-b= | | -8+t=-24 | | 74-6x=21x+17 | | 5-8x=69-22x | | -16=-x | | 4a(5a)= | | 6x+14=70-8x | | 15x-2=45x+16 | | (4a)(5b)= | | -8-5x=13-18x |

Equations solver categories